Antenna Design Using an Enhanced Multi‐Objective Artificial Hummingbird Algorithm Based on Tolerance Mechanism - Huang, Guan‐Long; He, Jin‐Peng; Qin, Peng‐Fei; Pang, Zi‐Yu; He, Xian‐Hui; Mahmoud, Abdelhady; Zeng, Jingtao; Yang, Hua (Microwave and optical technology letters, 2025)
ABSTRACT This letter presents a tolerance mechanism‐based enhanced multi‐objective artificial hummingbird algorithm (TM‐EMOAHA) for antenna optimization. The proposed method introduces an improved Pareto non‐dominated solution determination strategy with a tolerance mechanism to precisely define dominance relationships through objective prioritization. A hybrid perturbation strategy integrating polar coordinate transformation and objective‐oriented guidance is developed to enhance global search capability. The algorithm's effectiveness is demonstrated through a series‐fed patch antenna design case. Experimental results validate that compared with traditional multi‐objective algorithms, the TM‐EMOAHA obtains a series‐fed patch antenna with higher gain characteristics and lower sidelobe.